A Bridge Too Far? Examining Bridging Assumptions in Common‐Space Estimations. Issue 4 (18th December 2019) - Gray, Thomas R.; Jenkins, Jeffery A.
Abstract : While most common‐space estimations rely upon members who served in both the House and Senate as "bridges" to scale the remaining members, this assumes that these "bridge members" do not change their preferences when they change chambers. Such an assumption conflicts with standard notions of representation, that is, that legislators' votes reflect (at least to some degree) the wishes of their constituents. We examine the constancy of this common‐space voting assumption by focusing on a subset of House members who move to the Senate: those who come from statewide House districts. Using these members as the bridge actors—and thus bridging by constituency explicitly—in a one‐dimensional item response theory model, we find that the standard assumption of chamber switchers in common‐space estimations is technically, but immaterially, false. While there are statistically distinguishable differences in House and Senate voting records for chamber switchers, they are not sufficiently large to meaningfully undermine bridging.